1999
DOI: 10.1021/ac9810011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Acidic Polymers for Surface Acoustic Wave Vapor Sensors and Arrays

Abstract: Four hydrogen bond acidic polymers are examined as sorbent layers on acoustic wave devices for the detection of basic vapors. A polysiloxane polymer with pendant hexafluoro-2-propanol groups and polymers with hexafluorobisphenol groups linked by oligosiloxane spacers yield sensors that respond more rapidly and with greater sensitivity than fluoropolyol, a material used in previous SAW sensor studies. Sensors coated with the new materials all reach 90% of full response within 6 s of the first indication of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 37 publications
(56 reference statements)
1
101
0
Order By: Relevance
“…Also quadrol has also been used for the explosives detection 50 and fluoropolyol and its modified compound, viz., SXPHFA and SXFA on low-frequency devices 12,51 have also been reported. The most sensitive of the new polymers exhibit SAW sensor detection limits 14 for nitrobenzene and 2,4-dinitrolune at 3ppb, and 235 ppt respectively.…”
Section: Polymer-coated Saw Sensormentioning
confidence: 95%
“…Also quadrol has also been used for the explosives detection 50 and fluoropolyol and its modified compound, viz., SXPHFA and SXFA on low-frequency devices 12,51 have also been reported. The most sensitive of the new polymers exhibit SAW sensor detection limits 14 for nitrobenzene and 2,4-dinitrolune at 3ppb, and 235 ppt respectively.…”
Section: Polymer-coated Saw Sensormentioning
confidence: 95%
“…28,29 This polymer was rationally designed to have strongly hydrogen-bond acidic properties that are desirable for sorbing basic vapors. A great many basic organic solvents exist that are used industrially that one might want to detect.…”
Section: Diverse Sorbent Polymersmentioning
confidence: 99%
“…Accordingly, a number of synthetic materials have been prepared and investigated as sensor phases, most of which incorporate hexafluoroisopropanol moieties as the hydrogen-bond acidic group. [28][29][30][31][32][33][34][35][36][37][38][39] A study several years ago compared the hydrogen-bond acidities of several propyl-or allylsubstituted bisphenol structures using inverse gas chromatography and LSERs. 40 It was shown that fluorinated bisphenol-A structures were substantially more hydrogen-bond acidic than non-fluorinated analogs; fluorination improved sorption of basic compounds by factors of 100 or more.…”
Section: Figure 2 Four Examples Of Sorbent Polymers Prepared By Hydrmentioning
confidence: 99%
“…28,29,41 Figure 5 shows the calibration curves for SAW sensors coated with BSP3, fluoropolyol (FPOL), and polydimethylsiloxane (PDMS) when tested against dimethyl methylphosphonate, a nerve-agent simulant. FPOL is a sensor coating for nerve agents described in the past, 26,27,33,42 and PDMS serves as an example of a sorbent polymer lacking functionalities designed for sorption of basic vapors.…”
Section: Figure 3 Examples Of Monomers Used In Hydrosilylation Polymmentioning
confidence: 99%